PEREMPUAN DAN KETERWAKILANNYA DALAM POLITIK PRAKTIS - Hidayah, M.Si, Rifa (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2008)
Woman’s participation in political arena is facing marginalization. Although 30% regulation of women’s proportion in the parlementary has been implemented in 2004 general election, woman’s representative in political practice is still low. It just reached 11,8% from the targeted proportion (30%).For the next 2009 general election, all parties have not fulfilled the 30% proportion. The effort to reach 30% proportion of women's representative in the parliament should be implemented with the fact that women voter number is higher than men voter number. Through socialization of politics and women's representative issues, discrimination towards women's right maybe eliminated. Designing gender perspective curriculum and encouraging academicians to have gender sensitivity are importand effort too. Women are also expected to develop and to improve their capabilities including their intelectual and personal quality will support women's role significantly in political arena. Kata Kunci: Perempuan, keterwakilan perempuan dalam parlemen, politik praktis.